Edukasi Perilaku Hidup Sehat, Bersih, Dan Gizi Seimbang Sejak Dini - Salim, Reny (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Human behaviour is formed from habits carried out in everyday life. Habits come from knowledge or the process of imitation. Healthy, clean, and balanced nutrition habits are essential to be educated early, considering the many negative impacts that arise, such as infectious and non-communicable diseases. This negative impact reduces human competence and creativity. Aware of this, this service activity is carried out to know the behaviour, increase knowledge, and identify the nutritional status of service participants from an early age. Mitra Pengabdi is the Yayasan Prayoga, precisely SMP Yos Sudarso Padang. Participants in the activity are new learners. The service method is carried out in 3 stages, namely exploration, education, and testing. The results of this dedication are known that, in general, the daily behaviour of participants towards living healthy, clean, and balanced nutrition has followed the rules, but there are still those who need to. The knowledge of participants after education was 60% in the excellent category, 30% in the sufficient category, and 10% in the less category. Generally, the nutritional status of service participants is in the normal category, but they are still fat and thin. After participating in this service activity, participants are expected to be able to apply healthy, clean, and balanced nutrition behaviours adequately and appropriately so that they become models for individuals in the surrounding environment.